2013
DOI: 10.1186/1472-698x-13-36
|View full text |Cite
|
Sign up to set email alerts
|

Unintended pregnancies and the use of maternal health services in southwestern Ethiopia

Abstract: BackgroundThe benefits of maternal health care to maternal and neonatal health outcomes have been well documented. Antenatal care attendance, institutional delivery and skilled attendance at delivery all help to improve maternal and neonatal health. However, use of maternal health services is still very low in developing countries with high maternal mortality including Ethiopia. This study examines the association of unintended Pregnancy with the use of maternal health services in Southwestern Ethiopia.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
78
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 29 publications
(39 reference statements)
19
78
4
2
Order By: Relevance
“…In this study unplanned pregnancy was 29.9% among the study participants. This findings is in agreements with the findings from other studies in Ethiopia [36] and Kenya [18] but it is lower than the other studies that were conducted in Jimma 35% [37] and Hosana 34% [19], this might be due to the increased availability and accessibility of maternal health services, including access to modern family planning with time. More over this finding were much lower than the findings of studies conducted in Tanzania 45.9% [38] and Nepal 41.1% [35].…”
Section: Discussionsupporting
confidence: 91%
“…In this study unplanned pregnancy was 29.9% among the study participants. This findings is in agreements with the findings from other studies in Ethiopia [36] and Kenya [18] but it is lower than the other studies that were conducted in Jimma 35% [37] and Hosana 34% [19], this might be due to the increased availability and accessibility of maternal health services, including access to modern family planning with time. More over this finding were much lower than the findings of studies conducted in Tanzania 45.9% [38] and Nepal 41.1% [35].…”
Section: Discussionsupporting
confidence: 91%
“…Significantly higher rates of unwanted pregnancies in urban areas were reported among HIV uninfected women in India (Dixit et al, 2012) but not elsewhere (Kassa et al, 2012;Wado, Afework, & Hindin, 2013) suggesting similarity in the vulnerabilities and constraints among Indian urban women irrespective of their HIV status.…”
Section: Analysis Of First Pregnancy After Hiv Diagnosis (N=113)mentioning
confidence: 85%
“…Regarding both timing and number, the influence of female education was relatively stronger than wealth. Apart from the established fact that educated women are better informed about the colossal health benefits of first trimester and optimum ANC coverage and also inclined to comply with other health recommendations , they stand a better chance of being able to detect pregnancy early and subsequently avail themselves of early prenatal health services .…”
Section: Discussionmentioning
confidence: 99%
“…Much progress has been made globally towards increasing access to, and use of, ANC, although the overall proportion of women obtaining the WHO‐recommended minimum of four visits is still small . Similarly, it has been observed that women who seek antenatal care mostly do so later than within the recommended first 3 months of pregnancy (Central Statistical Authority Ethiopia and International, 2012, .…”
Section: Introductionmentioning
confidence: 99%